Animal factory : the looming threat of industrial pig, dairy, and poultry farms to humans and the environment - Kirby, David, 1960- (New York : St. Martin's Press, 2010)
Massive fish kills from flesh-eating parasites. Unusual concentrations of cancer and other diseases. Recalls of meats, vegetables, and fruits because of deadly E-coli bacterial contamination. Recent public health crises raise urgent questions about how our animal-derived food is raised and brought to market. This book is about our American food system gone terribly wrong--and the people who are fighting to restore sustainable farming practices and save our limited natural resources. Investigative journalist David Kirby exposes the powerful business and political interests behind large-scale factory farms, and tracks the far-reaching fallout that contaminates our air, land, water, and food. He follows three families and communities whose lives have been utterly changed by immense neighboring animal farms, turning them into unlikely activists.--From publisher description.
Includes bibliographical references (p. [453-474) ]and index.
Keywords: Factory farms -- Environmental aspects; Factory farms -- Health aspects